2014
DOI: 10.1159/000360607
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Is Not Associated with Inferior Pregnancy Rates in in vitro Fertilization: An Analysis of 616 Patients

Abstract: Background/Aims: To analyze whether the presence of endometriosis per se is associated with inferior pregnancy rates in women undergoing in vitro fertilization (IVF). Methods: Between July 2005 and November 2012, a total of 485 patients with endometriosis under the age of 38 years undergoing their first IVF attempt at our center were included; 72 patients had minimal-mild disease and the remaining 413 patients had moderate-severe disease. 131 patients with laparoscopically confirmed tubal factor infertility no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…We also found a significantly lower number of oocytes retrieved and mature oocytes in women with endometriosis, despite the higher gonadotropin doses used. This is in accordance with the available literature and is explained by the lower ovarian reserve in these patients [7][8][9][10][11][12]56]. Another added factor that could contribute to the lower oocyte yield is the difficult access to the follicles during retrievals in the presence of large endometriomas [57].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We also found a significantly lower number of oocytes retrieved and mature oocytes in women with endometriosis, despite the higher gonadotropin doses used. This is in accordance with the available literature and is explained by the lower ovarian reserve in these patients [7][8][9][10][11][12]56]. Another added factor that could contribute to the lower oocyte yield is the difficult access to the follicles during retrievals in the presence of large endometriomas [57].…”
Section: Discussionsupporting
confidence: 88%
“…Despite having a significant decrease in the quantitative IVF parameters assessed, we did not find any detrimental impact of endometriosis on oocyte maturity rate and cleavage rate, and multivariate analysis did not show any association between endometriosis and embryo quality. Our findings on the embryo quality are in accordance with several reports [11,16,30,[59][60][61][62][63][64][65] but contradictory to many others [10,13,[66][67][68][69]. The available data regarding time-lapse morphokinetic parameters are also heterogeneous.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, we had a good cumulative pregnancy rate and LBR in IVF. This is similar to the study of Polat et al (2014) [10], who concluded that women with endometriosis, regardless of the stage of the disease and its extent, had an IVF pregnancy rate and an IVF LBR equivalent to those of women with tubal infertility without endometriosis. We found three factors that significantly affected LBR after IVF-ICSI in women with rAFS stage III and IV endometriosis: active smoking, POR, and rAFS stage IV.…”
Section: Discussionsupporting
confidence: 90%
“…The suggested effect of endometriosis on pregnancy loss (33) could not be confirmed in our research. In contrast, the work of others was supported who published no such correlation between miscarriage rate and the presence of endometriosis (34,35). However, it has to be kept in mind that both miscarriage and malformation rate in the endometriosis cohort were markedly increased (although not to a significant level).…”
Section: Discussionmentioning
confidence: 95%